The risks of excessive use of contraceptives (Research, Society and Development, 2025)
Emergency contraception is a technique that can be used during unsafe sexual intercourse and also in situations of sexual violence. Excessive use of ec can cause various health problems and should only be used in critical situations. The goal is to reduce the incidence of unplanned pregnancies and abortions, as well as to limit maternal morbidity and mortality. The research seeks to detail the potential dangers associated with the use of emergency contraception, its most common side effects, and how it works. Therefore, an integrative review of the literature was conducted with a qualitative approach to the dangers of excessive use of emergency contraception. The risks of excessive contraceptive use were identified in the Scientific Electronic Library Online (SciELO) and Latin American and Caribbean Literature in Health Sciences (LILACS) databases, integrated into the Virtual Health Library (VHL). EC is a true hormonal injection and can contain up to ten times more hormones than traditional contraceptive methods. Abuse can result in various harms to the female body, side effects that include, in addition to nausea and vomiting, thromboembolism and other stress reactions, lactation, vaginal bleeding, fatigue, headache, dizziness, weakness, and pelvic pain. In short, EC's purpose is to prevent a potential unplanned pregnancy after unprotected sex, so it has its pros and cons. However, it should be used with caution, as it causes hormonal overload in the female body. Excessive use without prior knowledge can have serious consequences for the user, as it is a readily available drug.